Revisiting Drug Compliance: The Need for a Holistic Approach in the Treatment of Severe Mental Disorders - Mikhail Yu. Sorokin (Eco-Vector, 2021)
INTRODUCTION: The limited practice of depot antipsychotics and psychoeducation use, recommended for overcoming the noncompliance of patients with severe mental disorders, is linked to a high incidence of treatment violation. Therefore, the development of personalized mental healthcare approaches is a crucial healthcare task.